The Analysis of Language Style in the MULAN 2020 Movie - Ilham, Resky Febrianty; Dahniar, Dahniar; Nonci, Jusmaniar (English Literature Studi Program Universitas Islam Makassar, 2025)
This research is a sociolinguistic study focusing on movie language styles. This research aims to analyze the language styles of the Mulan 2020 movie and identify the context of the dominant language style used in the film. The researchers conducted this study using a descriptive qualitative method. This research involves multiple stages, including repeatedly watching the film to comprehend its content by concentrating on character dialogues and situational contexts. Subsequently, the researchers categorized the data for further analysis and adopts the applicable theory. This research uses the theory of language style from Martin Joos. The results of this study found four language styles with 74 data points, namely seven data points of the frozen style, thirty-nine data points of the formal style, twenty-three data points of the casual style, and five data points of the intimate style. The contextual use of this dominant language style is also diverse and often occurs in military situations, royal areas, formal situations, situations between Mulan and Xianniang as protagonists and antagonists, and informal situations. The use of this predominant language style generally serves the movie's storyline. These findings imply the influence of culture and social status on the prevalence of formal language styles in historically developed Asian movies, which serve functions outside formal situations.